2007
DOI: 10.1007/s11071-006-9189-7
|View full text |Cite
|
Sign up to set email alerts
|

Targeted energy transfers in vibro-impact oscillators for seismic mitigation

Abstract: In the field of seismic protection of structures, it is crucial to be able to diminish 'as much as possible' and dissipate 'as fast as possible' the load induced by seismic (vibration-shock) energy imparted to a structure by an earthquake. In this context, the concept of passive nonlinear energy pumping appears to be natural for application to seismic mitigation. Hence, the overall problem discussed in this paper can be formulated as follows: Design a set of nonlinear energy sinks (NESs) that are locally attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
115
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(118 citation statements)
references
References 29 publications
2
115
0
1
Order By: Relevance
“…This is expected, as the effectiveness of the linear attachment as shock absorber is narrowband and, as a result, its performance deteriorates away from the condition of linear resonance with the primary system. In contrast, the performance of the VI attachment is broadband [19,20], so that its effectiveness to passively absorb and dissipate shock energy extends over wider parameter ranges. With respect to the performance of the VI shock absorber (cf.…”
Section: Single-dof Oscillators With VI Attachmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is expected, as the effectiveness of the linear attachment as shock absorber is narrowband and, as a result, its performance deteriorates away from the condition of linear resonance with the primary system. In contrast, the performance of the VI attachment is broadband [19,20], so that its effectiveness to passively absorb and dissipate shock energy extends over wider parameter ranges. With respect to the performance of the VI shock absorber (cf.…”
Section: Single-dof Oscillators With VI Attachmentsmentioning
confidence: 99%
“…In an additional series of articles [10][11][12][13][14][15][16][17], VI dampers were considered to reduce the vibration levels of structures under periodic or stochastic excitation. In other works, VI devices have been applied to the problem of shock/seismic mitigation [18][19][20] and TET from structures to attached VI oscillators has been studied. In these words, it was shown that VI attachments are capable of absorbing broadband energy from a linear system at a fast time scale; this is critical in applications in which energy dissipation must occur at the initial phase of the motion where the energy is the highest.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the excess energy is retained within the NES itself [23]. This action leads to a reduction in the vibration amplitudes of the primary system in a broadband manner, which is due to the strong nonlinearity of the NES [24][25][26]. The energy dissipation rate of the primary structure can be controlled by adjusting the damping content of the NES [27].…”
Section: Introductionmentioning
confidence: 99%
“…Non-smooth nonlinear systems due their efficiency and feasibilities in fabrications and design are of highly interests in industrially [3]. Some research works have been carried to show the effectiveness of non-smooth NES devices in control of main structures [4][5][6][7][8]. However, some researches are carried to analyze and to consider the energy pumping phenomenon between a main non-smooth systems and coupled NES (essentially nonlinear or non-smooth) [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%